Fostering Teachers’ Competencies for Integrated Language Arts, Science, and Technology Instruction: An Exploratory Study - Rhodes, Miriam J.; Visscher, Adrie; van Keulen, Hanno; Gijsel, Martine (Journal of Teaching and Learning, 2025)
This study examined the impact of a teacher professional development (TPD) program on primary school teachers’ skills and self-efficacy in integrated language arts, science, and technology (ILS&T) instruction. The program’s design is based on the four-component instructional-design (4C/ID) model, validated in many areas for developing complex professional skills. Nine teachers from one primary school participated in five TPD group meetings during one school year. The TPD program focused on developing prerequisite skills for ILS&T instruction. Data were collected through lesson observations and interviews to assess teachers’ skills in ILS&T instruction, as well as through a self-efficacy questionnaire. Findings demonstrated varying proficiency levels in the required skills for ILS&T instruction among teachers after the program. This suggests that the program may have provided insufficient support for the development of some, potentially more complex, skills. Although teachers showed an overall increase in self-efficacy, the pre-post-test difference was not statistically significant. There were statistically significant increases in student engagement and instructional strategies subscales. This study discusses the exploratory impact of the TPD program for equipping teachers for ILS&T instruction. A discussion of the findings provides indications for optimizing the program for future large-scale implementation.